Quality of life and work productivity and activity impairment among online survey respondents with migraine across a range of headache frequency - Ishii, Ryotaro; Sakai, Fumihiko; Sano, Hiromi; Nakai, Masami; Koga, Nobuyuki; Matsukawa, Miyuki (Frontiers in Neurology, 2024)
Objective This study aimed to describe the migraine burden and healthcare utilization in the context of headache frequency using nationwide claims data linked to online survey data previously collected in Japan. Background It has been shown that increase in headache frequency can impose greater impact on individuals’ daily and social functioning, but migraine burden in those with low-frequency headaches remains largely unknown in Japan. Methods This post-hoc, observational study reported on 674 respondents who were working individuals and their family members aged 19–74 years, responded to an online questionnaire (response rate: 14.1% [21,704 responded/153,545 kencomⓇ registrants]), and were previously classified as having migraine. Disease burden in terms of Migraine-Specific Quality of Life (MSQ) and Work Productivity and Activity Impairment (WPAI) was compared across 0–3, 4–7, 8–14, and ≥ 15 monthly headache days (MHD). Results Among 674 respondents, 419 (62.2%), 148 (22.0%), 61 (9.1%), and 46 (6.8%) had 0–3, 4–7, 8–14, and ≥ 15 MHD, respectively. Of those, 55 (13.1%), 31 (20.9%), 19 (31.1%), and 20 (43.5%) respondents consulted physicians for headaches. Moderate-to-severe impairments in daily activities were reported by 298 (71.1%), 110 (74.3%), 46 (75.4%), and 38 (82.6%) respondents. The proportion of the respondents with WPAI >0% generally increased with increasing headache frequency (presenteeism: 41.7 and 67.5% in respondents with 0–3 and ≥ 15 MHD, respectively; overall work impairment: 44.8 and 72.5%, respectively; and activity impairment: 44.9 and 73.9%, respectively), except for absenteeism (12.4 and 22.5%, respectively). The mean MSQ score declined with increasing MHD (Role function-restrictive: 75.1 and 59.5 in those with 0–3 and ≥ 15 MHD, respectively; Role function-preventive: 85.8 and 75.0, respectively; and Emotional function: 81.9 and 63.6, respectively). Conclusion Based on the Japanese nationwide claims data, quality of life and work productivity decreased with increasing numbers of headache days. Substantial disease burden paired with low levels of healthcare utilization highlights the need for medical or non-medical intervention.